2015
DOI: 10.1080/1023666x.2015.1036219
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Opening Polymerization of Lactones Initiated with Metal Hydroxide-Activated Macrocyclic Ligands: Determination of Mechanism and Structure of Polymers

Abstract: Anhydrous alkali metal hydroxide (KOH, NaOH, and LiOH)-activated macrocyclic ligand complexing metal cations, i.e., coronands 12C4, 15C5, 18C6, DCH24C8, and cryptand C222, were selected for initiation of β-butyrolactone (β-BL) and ε-caprolactone (ε-CL) polymerization. It was found that β-BL polymerizes in the presence of KOH/18C6, KOH/C222, and NaOH/C222 systems. The real initiators in this case are two salts, potassium 3-hydroxybutyrate and potassium trans-crotonate, which are responsible for the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
(18 reference statements)
1
11
0
Order By: Relevance
“…Chromatographic analysis (GC-MS) of the reaction mixture indicated the formation of trans-crotonic acid isopropyl ester. Formation of macromolecules A and B was reported recently by us in the polymerization of β-BL initiated with anhydrous KOH activated 18C6 [13]. It indicated that KOH really formed in the studied systems and initiated β-BL polymerization.…”
Section: Reinvestigation Of Initiation Course Of β-Bl Polymerization supporting
confidence: 68%
See 3 more Smart Citations
“…Chromatographic analysis (GC-MS) of the reaction mixture indicated the formation of trans-crotonic acid isopropyl ester. Formation of macromolecules A and B was reported recently by us in the polymerization of β-BL initiated with anhydrous KOH activated 18C6 [13]. It indicated that KOH really formed in the studied systems and initiated β-BL polymerization.…”
Section: Reinvestigation Of Initiation Course Of β-Bl Polymerization supporting
confidence: 68%
“…In this case, only weak signals of macromolecules A were shown in MALDI-TOF spectrum. No signal of (CH 3 ) 3 CO-end group was found in 13 C NMR spectrum of the polymer. It indicates that t-butoxide anions behave during the initiation step mainly as a strong base.…”
Section: Reinvestigation Of Initiation Course Of β-Bl Polymerization mentioning
confidence: 89%
See 2 more Smart Citations
“…However, the application of NaH for ε-CL polymerization causes acyl-oxygen bond cleavage during initiation [19]. Recently [20], macrocyclic ligands activated by alkali metal hydroxides, i.e., LiOH, NaOH and KOH, have been used successfully for ε-CL polymerization. In all systems, initiation proceeded by acyl-oxygen bond cleavage.…”
Section: Introductionmentioning
confidence: 99%